Robinson w postantropocenie - Tomczok, Marta (Porównania, 2019)
This article attempts to explain the relationship between the expression „Robinson of Warsaw” and the novel Robinson Crusoe by Daniel Defoe and a contemporary reference to it in the futureska Two Ends of the World by Antoni Słonimski. The analytical part demonstrates the dependence of Słonimski’s prose on the role model and essay writing by Jan Kott and Ian Watt devoted to exceeding the individualistic perspective in the European novel. Towards the end, a question is asked about the preposterous reading of Two Ends of the World in the context of Rossi Braidotti’s concept of posthumanism.